Dimorphic glioblastoma with glial and epithelioid phenotypes: Clonal evolution and immune selection - Mondia, Mark Willy L.; Kritselis, Michael A.; Donahue, John E.; Elinzano, Heinrich; Sarangi, Sasmit; Bryant, David; Capelletti, Marzia; Korn, W. Michael; Yu, Esther; Yan, Sherry; Toms, Steven A.; Wong, Eric T. (Frontiers in Neurology, 2023)
Purpose: Epithelioid glioblastoma is an unusual histologic variant of malignant glioma. The present study investigates both the genomic and transcriptomic determinants that may promote the development of this tumor. Methods: Whole exome sequencing (WES) and whole transcriptome sequencing (WTS) were performed on an epithelioid glioblastoma, along with specific bioinformatic pipeline to generate electronic karyotyping and investigate the tumor immune microenvironment. Microdissected sections containing typical glioblastoma feature and epithelioid morphology were analyzed separately using the same methodologies. Results: An epithelioid glioblastoma, with immunopositivity for GFAP, Olig-2 and ATRX but negative for IDH-1 and p53, was identified. The tumor cell content from microdissection was estimated to be 85-90% for both histologic tumor components. WES revealed that both glioma and epithelioid sections contained identical point mutations in PTEN, RB1, TERT promoter and TP53. Electronic karyotype analysis also revealed similar chromosomal copy number alterations, but the epithelioid component showed additional abnormalities that were not found in the glioblastoma component. The tumor immune microenvironments were strikingly different and WTS revealed high levels of transcripts from myeloid cells as well as M1 and M2 macrophages in the glioma section, while transcripts from CD4+ lymphocytes and NK cells predominated in the epithelioid section. Conclusion: Epithelioid glioblastoma may be genomically more unstable, and oncogenically more advanced harboring an increased number of mutations and karyotype abnormalities, compared to typical glioblastomas. The tumor immune microenvironment is also different.